Latent moods in Heidegger and Sartre: from being assailed by moods to not conceding to (some) moods that assail us - Neuber, Simone (Philosophia, 2017)
This paper focusses on two prima facie independent assumptions of a - broadly - “Heideggerian” approach to moods: (i.) One concerning an apparent methodological impact of moods for a fundamental-ontological enterprise and (ii.) one concerning a presumed human tendency towards Verfallenheit (entanglement) or inauthenticity. It shows that the liaison of those two assumptions challenges theoretical claims according to which subjects are simply assailed by moods and passive with respect to being in a mood. To do so, it follows Heidegger’s reflections on the methodological impact of moods before turning to Heidegger’s considerations about the fundamental disclosure of what he calls the “burden of existence” in anxiety, a burden which - according to Heidegger - we tend to evade most of the time. This paper suggests that the “evasive” character of this tendency is linked to Heidegger’s claim that anxiety latently structures being-in-the-world and that Heidegger’s brief allusion to a difference between (i.) the fact of attuned disclosure and (ii.) conceding to a mood and to that which it discloses is his attempt to hint at what this ‘latency’ of anxiety might amount to. The focus, then, turns to Sartre, who not only shares Heidegger’s two assumptions but also emphasizes that if one wishes to make sense of such a structuring of life by a latent mood, a theory of moods should be saddled with a theory of la mauvaise foi, or self-deception in the broad sense.
Gesehen am 04.12.2019